Adat Pernikahan Mombolasuako pada Suku Tolaki dalam Tinjauan Hukum Islam - Muh Isra Syarif; Islahuddin Ramadhan Mubarak; Ihwan Wahid Minu (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This study aims to determine the review of Islamic law on the Mombolasuako Marriage Tradition in the Tolaki Tribe. This research is a field research. The type of research is a qualitative research type, with a juridical approach and a cultural anthropological approach. The results of the study show that, First, Mombolasuako or taking women away without the permission of their guardians to marry according to the Shari'a is prohibited and forbidden. So that a person should not choose the mombolasuako path when he wants to marry a woman, even though he is not approved. Second, the implementation of the Mombolasuako marriage custom of the Tolaki tribe in Konawe Regency, although it is not in accordance with the normal rules of Tolaki custom, but in the view of the Shari'a it is in accordance with Islamic Shari'a, because it fulfills the requirements and pillars of marriage in Islamic Shari'a, such as in a traditional procession. Mombolasuako which includes: (1) the Mepopolei stage which aims to ask for guardianship permission, so that it is accepted for the marriage process. (2) Then the mesokei stage, namely the stage where the agreed offerings are fulfilled, and this is the same as the dowry. (3) The last is the mowindahako stage, where the ijab qabul contract is carried out simultaneously with the presence of witnesses from adat.